2018
DOI: 10.1002/pola.29249
|View full text |Cite
|
Sign up to set email alerts
|

Radical polymerization of radical‐labeled monomers: The triarylmethyl‐based radical monomer as an example

Abstract: Recent development of spin-labeled nitroxide-mediated polymerization (NMP) involving successful polymer preparation with high livingness and narrow dispersity in the presence of persistent trityl-based stable radicals attached to the initiators (90% recovery of a trityl radical signal after the polymerization) led us to the preparation of stable organic radical polymers based on trityl radical-substituted monomers using NMP as the method of polymerization despite the claims in the literature about its expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, to use trityl-based persistent hydrocarbon radicals in this strategy, a functional group would need to be introduced before generating the radical (pre-modification) for avoiding rapid decomposition, 16 and the post-modification of the persistent radicals is still limited. 17 To explore this strategy, we examined reactions of radical 1 involving in situ removal of the silyl group using TBAF and subsequent [4+2] Diels–Alder reaction using tetraphenylcyclopentadienone (tetracyclone) (Scheme 3). We observed that this process leads to formation of the tetraphenylphenyl substituted TAntM radical 2 in 37% yield.…”
mentioning
confidence: 99%
“…However, to use trityl-based persistent hydrocarbon radicals in this strategy, a functional group would need to be introduced before generating the radical (pre-modification) for avoiding rapid decomposition, 16 and the post-modification of the persistent radicals is still limited. 17 To explore this strategy, we examined reactions of radical 1 involving in situ removal of the silyl group using TBAF and subsequent [4+2] Diels–Alder reaction using tetraphenylcyclopentadienone (tetracyclone) (Scheme 3). We observed that this process leads to formation of the tetraphenylphenyl substituted TAntM radical 2 in 37% yield.…”
mentioning
confidence: 99%
“…Owing to its suitable activation–deactivation properties, trityl group has been employed for the synthesis of various complex macromolecular structures as a notable control agent . In an attempt to extend its practices and combinations with other polymerization techniques, herein a novel “grafting from” approach is reported.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the literature, it was quoted [ 76 , 77 ]: “free-radical polymerization techniques cannot be used in the direct polymerization method” which is in sharp contrast with our claims concerning SL-NMP. Therefore, two types of trityl monomers were prepared—a trityl radical 9 carrying three acrylamides as monomer units and a trityl radical 10 carrying one unit of acrylamide as monomer—and were investigated in conventional polymerization and in NMP ( Figure 12 ) [ 78 ]. Depending on the experimental conditions, up to 90% of trityl radicals were recovered both in crude and purified materials.…”
Section: Spin Labeled Nitroxide Mediated Polymerization Sl-nmpmentioning
confidence: 99%
“…Preparation of stable organic radical polymer (SORP) using conventional radical polymerization and NMP. Reprinted with the permission of Wiley from ref [78]…”
mentioning
confidence: 99%